2021
DOI: 10.2147/clep.s305126
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Risk Associated with Methotrexate versus Retinoids in Patients with Psoriasis: A Nationwide Taiwanese Cohort Study

Abstract: Purpose Psoriasis is an inflammatory disease associated with cardiovascular disease. Methotrexate (MTX) is a first-line systemic anti-psoriatic agent that may also protect against cardiovascular disease. We examined the cardiovascular risks among patients with psoriasis who were receiving MTX or the comparator, retinoids. Patients and Methods We analysed data from the Taiwanese National Health Insurance database. The primary outcome was a composite of hospitalisation fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
(100 reference statements)
0
9
0
Order By: Relevance
“…Based on the presumed association between psoriasis and CCVD, several studies explored the effects of systemic antipsoriatic therapies on CCVD risk in psoriasis patients. Regarding conventional antipsoriatic agents, a few studies demonstrated the protective effect of methotrexate against CCVD development 19,20 . Moreover, some data indicated a cardioprotective effect of biologics in psoriasis patients 13,21 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Based on the presumed association between psoriasis and CCVD, several studies explored the effects of systemic antipsoriatic therapies on CCVD risk in psoriasis patients. Regarding conventional antipsoriatic agents, a few studies demonstrated the protective effect of methotrexate against CCVD development 19,20 . Moreover, some data indicated a cardioprotective effect of biologics in psoriasis patients 13,21 .…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al found that anti‐TNF‐treated psoriasis patients had a decreased incidence of myocardial infarction as compared to those treated with only topical agents 12 . Despite the reported cardioprotective effects of a few treatment modalities for psoriasis in these studies, they had some limitations, including the enrollment of patients with rheumatoid arthritis as well as psoriasis patients, 19 the focus on the use of a single systemic antipsoriatic agent for a short treatment duration, or limited follow‐up periods 12,13,20,21 . Considering real‐world characteristics of psoriasis treatment, such as long‐term treatment, rotational or sequential treatment using various treatment modalities, and intermittent treatment to avoid the side effects during long‐term use of a single antipsoriatic treatment, 22–24 the cardioprotective effects of systemic antipsoriatic therapies in psoriasis patients can be properly investigated through an analysis that incorporates all systemic antipsoriatic therapies used in each patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the same study by Lan et al, retinoid therapy showed no variability in the risk of cerebrovascular disease development [ 71 ]. Retinoids have been shown to be less effective in yet another cohort study by Tsai et al, who found that there was a lower incidence of adverse cardiovascular outcomes, ischemic stroke, ischemic heart disease, and total mortality with methotrexate when compared to retinoids [ 73 ]. From the calcineurin inhibitor family, the T cell-inhibiting drug cyclosporine is also used for psoriasis treatment [ 11 ].…”
Section: Reviewmentioning
confidence: 99%